Molecular Characterization of an Isoflavone 2′-Hydroxylase Gene Revealed Positive Insights into Flavonoid Accumulation and Abiotic Stress Tolerance in Safflower - Jianyu Liu; Naveed Ahmad; Yingqi Hong; Meihua Zhu; Shah Zaman; Nan Wang; Na Yao; Xiuming Liu (Molecules, 2022)
Flavonoids with significant therapeutic properties play an essential role in plant growth, development, and adaptation to various environments. The biosynthetic pathway of flavonoids has long been studied in plants; however, its regulatory mechanism in safflower largely remains unclear. Here, we carried out comprehensive genome-wide identification and functional characterization of a putative cytochrome P45081E8 gene encoding an isoflavone 2′-hydroxylase from safflower. A total of 15 CtCYP81E genes were identified from the safflower genome. Phylogenetic classification and conserved topology of CtCYP81E gene structures, protein motifs, and cis-elements elucidated crucial insights into plant growth, development, and stress responses. The diverse expression pattern of CtCYP81E genes in four different flowering stages suggested important clues into the regulation of secondary metabolites. Similarly, the variable expression of CtCYP81E8 during multiple flowering stages further highlighted a strong relationship with metabolite accumulation. Furthermore, the orchestrated link between transcriptional regulation of CtCYP81E8 and flavonoid accumulation was further validated in the yellow- and red-type safflower. The spatiotemporal expression of CtCYP81E8 under methyl jasmonate, polyethylene glycol, light, and dark conditions further highlighted its likely significance in abiotic stress adaption. Moreover, the over-expressed transgenic Arabidopsis lines showed enhanced transcript abundance in OE-13 line with approximately eight-fold increased expression. The upregulation of AtCHS, AtF3′H, and AtDFR genes and the detection of several types of flavonoids in the OE-13 transgenic line also provides crucial insights into the potential role of CtCYP81E8 during flavonoid accumulation. Together, our findings shed light on the fundamental role of CtCYP81E8 encoding a putative isoflavone 2′-hydroxylase via constitutive expression during flavonoid biosynthesis.